Effects of eccentricity on the seismic rehabilitation performance of nonseismically detailed interior beam-wide column joints - Li, Bing (2012)
In this paper, the effects of the eccentricity on the effectiveness of fiber-reinforced polymers (CFRP) or glass fiber reinforced polymer (GFRP) in repairing the shear strength and ductility of nonseismically detailed beam-wide column joints have been evaluated. For this purpose, four (two concentric and two eccentric) full-scale nonseismically detailed interior beam-wide column joints were used as control specimens. All four subassemblages were subjected to similar cyclic lateral displacement so as to provide the equivalent of severe earthquake damage. The damaged control specimens were then repaired by filling their cracks with epoxy and externally bonding them with CFRP sheets and GFRP sheets. These repaired specimens were then re-tested and their response histories were obtained. Hence, a total of eight specimens were tested: four control, and four repaired. The response histories of the control and repaired specimens were then compared. The results were compared through hysteretic loops, load-displacement envelopes, energy dissipation capacity, secant stiffness degradation, and shear strength and damage indices. Moreover, the effectiveness of the proposed repair schemes in repairing the eccentric and concentric joints was also compared. The present study demonstrates that proposed repair schemes can recover the performance of both damaged RC concentric and eccentric beam-wide column joints effectively.